Uso de agroquímicos como posible medida de control de la "escoba de bruja" (Crinipellis perniciosa) del cacao (1990)
An experiment was carried out to find an alternative for the control of Crinipellis perniciosa. The systemic fungicides pyracarbolid, oxicarboxin, triadimephon and a mineral oil were evaluated under field conditions. Three types of brooms were sprayed twice during the highest peak of sporulation. A high inhibition of sporulation was observed with mineral oil alone or mixed with fungicides. Good sporulation inhibition was also observed when oxicarboxin was applied in water. Sporulation of brooms on trees was lower in those sprayed with oil or fungicides in oil. Green and dry brooms detached from trees and hugh up under the canopy, produced significantly fewer basidiocarps than the control. An integrated program of control could be used taking in consideration the fungicide effectivity, spray cover and disease cycle.